2012
DOI: 10.1371/journal.pgen.1003084
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Biochemical Dissection of a HisKA Domain Identifies Residues Required Exclusively for Kinase and Phosphatase Activities

Abstract: Two-component signal transduction systems, composed of histidine kinases (HK) and response regulators (RR), allow bacteria to respond to diverse environmental stimuli. The HK can control both phosphorylation and subsequent dephosphorylation of its cognate RR. The majority of HKs utilize the HisKA subfamily of dimerization and histidine phosphotransfer (DHp) domains, which contain the phospho-accepting histidine and directly contact the RR. Extensive genetics, biochemistry, and structural biology on several pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
119
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(133 citation statements)
references
References 43 publications
13
119
1
Order By: Relevance
“…The E/D residue is required for kinase and N/T for phosphatase activities, respectively [64,65]. Experimentally, it was demonstrated that the recombinant cytoplasmic fragment of HaeS uses ATP as the phosphodonor to autophosphorylate the conserved histidine 226 residue, while a recombinant cytoplasmic fragment of HaeS carrying the H226A point mutation was not phosphorylated.…”
Section: Haesr Systemmentioning
confidence: 99%
“…The E/D residue is required for kinase and N/T for phosphatase activities, respectively [64,65]. Experimentally, it was demonstrated that the recombinant cytoplasmic fragment of HaeS uses ATP as the phosphodonor to autophosphorylate the conserved histidine 226 residue, while a recombinant cytoplasmic fragment of HaeS carrying the H226A point mutation was not phosphorylated.…”
Section: Haesr Systemmentioning
confidence: 99%
“…We were unable to perform the converse experiment by selectively eliminating phosphatase activity. In some sensor kinases it has been shown that within a conserved E/DxxT motif of the DHp domain, the Thr residue is critical for phosphatase activity (Huynh & Stewart, 2011;Willett & Kirby, 2012). FeuQ shares this conserved motif, but mutations to the conserved Thr did not give a phenotype consistent with eliminated phosphatase activity (data not shown).…”
Section: Discussionmentioning
confidence: 95%
“…We performed random mutagenesis of feuQ searching for 'FeuN-insensitive' (constitutively activating) and 'FeuN-mimicking' (constitutively inhibiting) alleles that might reveal domains of the FeuQ protein that are important for potential FeuN interaction and toggling between kinase and phosphatase activities. We expected to find mutations leading to each phenotype in the HAMP, DHp and CA domains, as these regions are known to be involved in SK signal integration (Atkinson & Ninfa, 1993;Hsing et al, 1998;Willett & Kirby, 2012). We suspected that mutations might also correspond to the FeuQ periplasmic domain, where FeuQ and FeuN are most likely to directly interact.…”
Section: Feuq Mutations Lead To Both Feun-insensitive and Feun-mimickmentioning
confidence: 98%
“…Proteins were radiolabeled with acetyl phosphate ([ 32 P]AcP) as described previously (10,24). Briefly, [ 32 P]AcP was generated using E. coli acetate kinase (Sigma).…”
Section: Methodsmentioning
confidence: 99%